PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN TRUST TERHADAP LOYALITAS DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING PADA PT. BANK CENTRAL ASIA CABANG SITUBONDO - Sanjaya, Lely Darmawan Parawangsa; Karnadi, Karnadi; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The aim of this research is to analyze the influenceThe Influence of Service Quality, Product Quality and Trust on Loyalty and Customer Satisfaction as Intervening Variables at PT. Bank Central Asia Situbondo Branch. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Service quality has a significant positive effect on Satisfaction (H1 is accepted), Product quality has a significant positive effect on Satisfaction (H2 is accepted), Trust has a significant positive effect on Satisfaction (H3 is accepted), Service quality has a positive but not significant effect on Loyalty (H4 is rejected), Quality product has a positive but not significant effect on Loyalty (H5 is rejected), Trust has a positive but not significant effect on Loyalty (H6 is rejected), Satisfaction has a significant positive effect on Loyalty (H7 is accepted), Service quality has a significant positive effect on Loyalty through Satisfaction (H8 is accepted), Product quality has a significant positive effect on Loyalty through Satisfaction (H9 is accepted), and Trust has a significant positive effect on Loyalty through Satisfaction (H10 is accepted).